2003
DOI: 10.1046/j.1444-1586.2003.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of lipoprotein(a) in carotid plaque types and ischemic stroke in the elderly

Abstract: Background:  The relationship between lipoprotein(a) (Lp(a)) and ischemic stroke is still controversial in the elderly. The purpose of the present paper was to evaluate the significance of Lp(a) in the development of extracranial carotid lesions and ischemic stroke. Methods:  A total of 371 elderly subjects, studied with carotid ultrasonography (US) and brain computed tomography (CT), was stratified into two groups according to serum Lp(a) levels: the normal Lp(a) and high Lp(a) (>40 mg/dL) groups. Carotid pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our study, the high Lp(a) level group (40 mg/dL or more) was separated from the normal group since the frequency of Lp(a) level =40 mg/dL was significantly different between the AD and control groups, and the Lp(a) level of 40 mg/dL was considered to be a threshold. Uniformly accepted standards of Lp(a) levels are lacking, but an apparent threshold for coronary risk is also recognized at Lp(a) levels of 30–40 mg/dL, and such levels were observed in approximately 20% of subjects studied 6,13 . Serum Lp(a) concentration depends on apoprotein(a) size polymorphism and is constant throughout life within an individual 6,7 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, the high Lp(a) level group (40 mg/dL or more) was separated from the normal group since the frequency of Lp(a) level =40 mg/dL was significantly different between the AD and control groups, and the Lp(a) level of 40 mg/dL was considered to be a threshold. Uniformly accepted standards of Lp(a) levels are lacking, but an apparent threshold for coronary risk is also recognized at Lp(a) levels of 30–40 mg/dL, and such levels were observed in approximately 20% of subjects studied 6,13 . Serum Lp(a) concentration depends on apoprotein(a) size polymorphism and is constant throughout life within an individual 6,7 …”
Section: Discussionmentioning
confidence: 99%
“…Uniformly accepted standards of Lp(a) levels are lacking, but an apparent threshold for coronary risk is also recognized at Lp(a) levels of 30-40 mg/dL, and such levels were observed in approximately 20% of subjects studied. 6,13 Serum Lp(a) concentration depends on apoprotein(a) size polymorphism and is constant throughout life within an individual. 6,7 A relationship between ApoE and the Lp(a) metabolisms has been described, 16 while a recent study 17 showed no independent effect of ApoE polymorphism on the Lp(a) level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations